Customer loyalty: effects of sales information system, marcomm, and brand ambassadors - Indrasari, Meithiana; Hapsari, Intan Nursini; Sukesi, Sukesi (Jurnal Studi Komunikasi, 2019)
Cosmetic products have different characteristics compared to other products. Recently, it is considered as primary needs rather than secondary which are always included in the monthly shopping list. Without leaving its identity, the company is based on multi-level marketing, which previously was a negative image. Oriflame required to satisfy customers so that they can get loyal customers. This research will analyse the influence of Sales Information System, IMC Strategy (Integrated Marketing Communications) and the Role of Brand Ambassadors on the loyalty of customers of Oriflame products in Indonesia. To obtain data for analysis, this research conducts the non-probability sampling method of purposive sampling, which is a method of determining respondents to be sampled. The population in this study are all customers of Oriflame products in Indonesia.